2020
DOI: 10.15359/rcv.38-1.1
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos epidemiológicos de la brucelosis en humanos en las Áreas Rectoras Aguas Zarcas y Los Chiles, Costa Rica, 2015-2017

Abstract: La brucelosis es una enfermedad zoonótica causada por especies del género Brucella spp., con baja notificación y subregistro en Costa Rica, especialmente en personas y en bovinos. Se determina la seroprevalencia para Brucella spp. lisas y factores de riesgo asociados, en personas que habitan o trabajan en fincas ganaderas positivas a brucelosis bovina de las Áreas Rectoras de Salud de Aguas Zarcas y Los Chiles, Alajuela, entre 2015 y 2017, mediante un estudio transversal analítico. Se toma una muestra sanguíne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
2
0
2
Order By: Relevance
“…In 2015, a randomized trial carried out in Costa Rica’s Huetar Norte Region (170 inhabitants) found human brucellosis prevalence at 12.5% among rural at-risk people. A Ministry of Health report confirmed that 144 human brucellosis cases had been reported for the entire country (at the time having 4.5 million inhabitants) but there had been only eight reported for the same northern region [ 68 ]. Additionally, inconsistent numbers have also been found in Colombia and Mexico [ 69 , 70 ], as well as other countries [ 71 ] that provide a similar picture.…”
Section: Prevalence Of Human Brucellosismentioning
confidence: 99%
“…In 2015, a randomized trial carried out in Costa Rica’s Huetar Norte Region (170 inhabitants) found human brucellosis prevalence at 12.5% among rural at-risk people. A Ministry of Health report confirmed that 144 human brucellosis cases had been reported for the entire country (at the time having 4.5 million inhabitants) but there had been only eight reported for the same northern region [ 68 ]. Additionally, inconsistent numbers have also been found in Colombia and Mexico [ 69 , 70 ], as well as other countries [ 71 ] that provide a similar picture.…”
Section: Prevalence Of Human Brucellosismentioning
confidence: 99%
“…However, when the figures of both sources are contrasted with field studies, it becomes evident that a significant proportion of the official data lacks precision. For example, while a randomized study in a rural at-risk population in the Huetar Norte Region of Costa Rica (170 inhabitants) estimated the human brucellosis prevalence at 12.5% (the year 2015), the Ministry of Health reported a total of 144 human brucellosis cases for the whole country (then with 4.5 million inhabitants), and only eight cases for the same northern region [ 69 ]. Similarly, discordant figures have been found in countries such as Colombia and México [ 70 , 71 ] and elsewhere [ 14 ].…”
Section: The Conundrums Of Human Brucellosismentioning
confidence: 99%
“…Sin embargo, existen otras vías de infección como la respiratoria (inhalación de polvo, pelo, excretas de animales infectados), cutánea y conjuntival (contacto directo con material contaminado). De modo que la asistencia en los partos, faena de animales y limpieza de los utensilios, máquinas y vertederos son las actividades más involucradas en la transmisión del patógeno (6,8) .…”
Section: Introductionunclassified
“…Entre ellas, se encuentran las pruebas tamiz como Rosa de Bengala y Huddleson, siendo las más empleadas para detectar inmunoglobulinas M y G contra la Brucella sp. (8) .…”
Section: Introductionunclassified